CURRENT STATUS OF RISK FACTORS FOR TYPE 2 DIABETES MELLITUS AMONG ADULTS AGED 18-69 IN HANOI (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the current status of several risk factors for type 2 diabetes mellitus and analyze factors associated with these risk factors among people aged 18-69 years in Hanoi in 2023.Subject and methods: A cross-sectional descriptive study was conducted on 745 participants aged 18-69.Results: The study revealed that 33.3% of participants consumed the recommended amount of fruits and vegetables, 82.1% were non-smokers, and 85.9% limited alcohol consumption, while 41.9% achieved sufficient physical activity. Multivariable logistic regression analysis showed that males had higher odds of smoking, high-risk alcohol consumption, and inadequate fruit and vegetable intake than females (p < 0.05). Males were also more likely than females to achieve sufficient physical activity. Participants with an education level below high school had 1.66-fold higher odds of smoking compared with those with a higher educational level. Smokers had higher odds of high-risk alcohol consumption than non-smokers (OR = 8.45; p < 0.05). A higher proportion of participants with type 2 diabetes mellitus achieved sufficient physical activity compared with those without the disease.Conclusion: Several risk factors for type 2 diabetes mellitus remain prevalent in the study area. Therefore, it is necessary to strengthen health education, nutrition counseling, and lifestyle interventions.
Keywords: Type 2 diabetes mellitus, risk factors, adults aged 18-69.